Antifungal Activity of Essential Oils against Fluconazole Resistant Fungi - Alpa Gopal Rabadia; Sheela D. Kama; Dilip V. Kamat (International Journal of Phytomedicine, 2011)
Pathogenic fungi like Candida albicans, Candida tropicalis and Trichophyton mentagrophytes are commonly encountered strains associated with a wide range of conditions including scalp infection, oral thrush, skin infection, and vaginal thrush. Unlike bacterial pathogens, fungal pathogens are difficult to control. Fluconazole is a commonly administered antifungal drug. The medical fraternity has been reporting an alarming increase in the development of resistance observed amongst fungal strains to Fluconazole. The present study involves screening of essential oils for their antifungal activity against Fluconazole resistant fungi. Essential oils of Black pepper, Cardamom, Cumin, Boswellia and Patcholi were selected for the study. The results indicated that all the oils inhibited fungal strains in varying degrees of dilutions. Essential oil of Boswellia was found to be the most effective in antifungal activity against Candida tropicalis and essential oil of Cardamom against Trichophyton mentagrophytes. To assess the effect of combination of essential oils with Fluconazole, synergistic action was also studied. The results indicated that essential oil of Boswellia and Fluconazole in combination acted as the most powerful antifungal agent against Candida tropicalis even at 1:10 dilution and 100μg/ml respectively. These results lead us to believe that active components present in essential oils should be a focus area of future in vivo research, especially in conjunction with existing antifungal drugs. The molecular mechanisms, mode of action, stability, toxicity, and efficacy of the active components isolated from essential oils need to be further studied and evaluated.